Influence of plant spacing and sowing time on yield of sunflower (Helianthus annus L.) - Baghdadi, Ali; Abd Halim, Mohd Ridzwan; Nasiri, Alireza; Ahmad, Izham Hazizi; Aslani, Farzad (WFL Publisher, 2014)
Sunflower production can be increased by optimizing agronomic practices that affect production. Plant spacing and sowing time are two important factors affecting sunflower production. To determine the optimum sowing date and plant spacing of native sunflower, an experiment was conducted for one year at the Research Farm of Agricultural Research Center in Rasht, located in north of Iran. Climatically, the area has a mild and humid climate with variable rainfall throughout the year. The average rainfall during the year is 1359 mm. The experiment was laid out as a randomized complete block design with three replications. The treatments were two planting dates (25th April and 15th May), and four plant spacing (75 cm ×20 cm, 65 cm ×23 cm, 50 cm ×30 cm, 35 cm ×43 cm) with equal plant density. The results showed significant effects of planting date and plant spacing on yield and yield components of native sunflower. The earlier planting date was shown to give better seed yields than later planting. The later planting date resulted in decreased yield of sunflower but increased straw yield. Also number of infertile seeds/head was lower at the early planting time. At all plant spacing the early planting gave a superior harvest index compared to the later planting. Increasing row spacing resulted in increasing yield. The highest seed yield (2489 kg/ha) and harvest index (18.93%) were obtained from the early planting date at the 75 cm ×20 cm plant spacing. A delay of the planting date significantly decreased grain yield of sunflower due to a decrease in the number of seeds per head and in seed weight and seed yield.